2010
DOI: 10.1007/s00468-010-0420-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of climate, tree age, dominance and growth on δ15N in young pinewoods

Abstract: . Effects of climate, tree age, dominance and growth on δ 15 N in young pinewoods. Trees 24, 507-510. AbstractNeedles, annual rings from basal stem disks and bark of 3 dominant and 3 suppressed Pinus pinaster from a 12-year-old pine stand (naturally regenerated after a wildfire) were analysed to study the effects of climate, tree age, dominance and growth on tree δ 15 N. Foliar-N concentration in dominant pines (0.780-1.474 % N) suggested that soil N availability was sufficient, a circumstance that allowed iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 50 publications
4
8
1
Order By: Relevance
“…The linear regression models showed that both biotic (dominance and tree age) and abiotic factors (temperature in spring-summer and annual precipitation) are needed to explain the wood  15 N air satisfactorily. Although Couto-Vázquez and González-Prieto (2010) found that tree age explained almost half of wood  15 N air variance of dominant and suppressed P. pinaster when separately considered, we only found a valid model for dominant trees with age or its inverse (1/age) explaining 34-39 % of the variance. In the best multiple regression model we obtained, explaining half the variance of wood  15 N air , the inverse of tree age has a higher standardized coefficient (0.578) than temperature in spring-summer (0.393).…”
Section: N Natural Abundancecontrasting
confidence: 74%
See 1 more Smart Citation
“…The linear regression models showed that both biotic (dominance and tree age) and abiotic factors (temperature in spring-summer and annual precipitation) are needed to explain the wood  15 N air satisfactorily. Although Couto-Vázquez and González-Prieto (2010) found that tree age explained almost half of wood  15 N air variance of dominant and suppressed P. pinaster when separately considered, we only found a valid model for dominant trees with age or its inverse (1/age) explaining 34-39 % of the variance. In the best multiple regression model we obtained, explaining half the variance of wood  15 N air , the inverse of tree age has a higher standardized coefficient (0.578) than temperature in spring-summer (0.393).…”
Section: N Natural Abundancecontrasting
confidence: 74%
“…As also reported in most ecosystems studied (see Högberg 1997), all plant material was 15 N-depleted compared with the  15 N air of the bulk soil in the 0-30 cm layer. While in suppressed pines the  15 N air was significantly higher in wood than in needles and bark, no differences were found for dominant trees; thus, no common trend for different coniferous species or sites (Nadelhoffer et al 1999;Couto-Vázquez and González-Prieto 2010) and dominance status can be derived.…”
Section: N Natural Abundancementioning
confidence: 81%
“…It is also possible that the balance between the supply and use of NSC (Deckmyn et al . ), as well as the uptake and allocation of N (Couto‐Vázquez & González‐Prieto ) differ among trees of different crown classes, thus affecting NSC and N concentrations, and rates of R of dominant, co‐dominant and suppressed trees.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike previous studies, we suggest that direct comparison of the total N concentration of untreated and pre‐treated ring samples is less meaningful, since the weight loss (removed non‐N components by toluene‐ethanol solution) upon removal is not evaluated. On the contrary, such a removal influences the δ 15 N values, since wood components (tannins, polyphenols, fats, waxes, resins, alkaloids, etc …”
Section: Discussionmentioning
confidence: 82%